2016
DOI: 10.1007/s11356-016-6055-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community compositions in sediment polluted by perfluoroalkyl acids (PFAAs) using Illumina high-throughput sequencing

Abstract: The characterization of bacterial community compositions and the change in perfluoroalkyl acids (PFAAs) along a natural river distribution system were explored in the present study. Illumina high-throughput sequencing was used to explore bacterial community diversity and structure in sediment polluted by PFAAs from the Xiaoqing River, the area with concentrated fluorochemical facilities in China. The concentration of PFAAs was in the range of 8.44-465.60 ng/g dry weight (dw) in sediment. Perfluorooctanoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(15 citation statements)
references
References 60 publications
1
10
1
1
Order By: Relevance
“…However, the effects of perfluoroalkyl substances on fungal stress responses and the fungal transformation of 6:2 FTOH and related compounds has not yet been examined. Comparatively, bacteria (e.g., Dehalococcoides and Rhodococcus jostii RHA1) were negatively impacted by perfluoroalkyl acids (Weathers, Harding‐Marjanovic, Higgins, Alvarez‐Cohen, & Sharp, ; Weathers, Higgins, & Sharp, ), and the bacterial community in aerobic river sediment was observed to decrease in diversity with PFOA exposure (>100 nanograms per gram dry weight in sediment; Sun, Wang, Peng, Wang, & Lu, ). Hydrogenotrophic methanogens from anaerobic sludge were also inhibited by 500 mg PFOS/L, but other PFASs tested, such as PFBS, PFPrA, and PFPeA, did not inhibit methanogenesis (Ochoa‐Herrera, Field, Luna‐Velasco, & Sierra‐Alvarez, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of perfluoroalkyl substances on fungal stress responses and the fungal transformation of 6:2 FTOH and related compounds has not yet been examined. Comparatively, bacteria (e.g., Dehalococcoides and Rhodococcus jostii RHA1) were negatively impacted by perfluoroalkyl acids (Weathers, Harding‐Marjanovic, Higgins, Alvarez‐Cohen, & Sharp, ; Weathers, Higgins, & Sharp, ), and the bacterial community in aerobic river sediment was observed to decrease in diversity with PFOA exposure (>100 nanograms per gram dry weight in sediment; Sun, Wang, Peng, Wang, & Lu, ). Hydrogenotrophic methanogens from anaerobic sludge were also inhibited by 500 mg PFOS/L, but other PFASs tested, such as PFBS, PFPrA, and PFPeA, did not inhibit methanogenesis (Ochoa‐Herrera, Field, Luna‐Velasco, & Sierra‐Alvarez, ).…”
Section: Resultsmentioning
confidence: 99%
“…Effect of PFOA and PFOS on growth of fungal isolates PFOA and PFOS by the six fungal isolates was examined. Fungi wereSharp, 2015), and the bacterial community in aerobic river sediment was observed to decrease in diversity with PFOA exposure (>100 nanograms per gram dry weight in sediment;Sun, Wang, Peng, Wang, & Lu, 2016). Hydrogenotrophic methanogens from anaerobic sludge were also inhibited by 500 mg PFOS/L, but other PFASs tested, such as PFBS, PFPrA, and PFPeA, did not inhibit methanogene-…”
mentioning
confidence: 99%
“…strain CPB4337 (Rosal et al ., ), cause membrane disruption, oxidative stress and DNA damage in Escherichia coli bacteria (Liu et al ., ), and that they influence bacterial membrane fluidity, permeability and quorum sensing (Fitzgerald et al ., , ). Furthermore, there is a 16S rRNA gene survey indicating that these compounds can drive selective changes in bacterial sediment communities (Sun et al ., ). In the current study, we found no growth responses of bacteria in exponential phase to the combination of PFOS and PFOA and only a very minor difference for bacteria in stationary phase.…”
Section: Discussionmentioning
confidence: 97%
“…Concentrations of PFOA in water from the Xiaoqing River basin ranged from 38.6 to 1,707,290 ng L À1 (Liu et al, 2016). The greatest concentrations of PFASs in sediment were detected in the Xiaoqing River, of which PFOA was dominant and its concentrations were between 3.86 and 456.20 ng g À1 dw (Sun et al, 2016). In addition, studies in the Liaohe, Haihe and Yellow Rivers were also carried out (Li et al, 2011;Pan et al, 2011b;Wang et al, 2012aWang et al, , 2012bYang et al, 2011;Zhao et al, 2013).…”
Section: Fluorinated Pops In Environmentmentioning
confidence: 99%